Reproductive tract infections associated with vaginal discharge and their socio-demographic and reproductive determinants among clinic attendees in Bangladesh (South East Asia Journal of Public Health, 2013)
Abnormal vaginal discharge is frequently associated with common sexually and non-sexually transmitted reproduc-tive tract infections (RTIs) and the resultant poor reproductive health outcomes. However, there is scarce informa-tion concerning the prevalence and etiologies of these infections in women in Bangladesh. The aim of study was to determine the rates of, and socio-demographic and reproductive characteristics associated with, common RTIs in urban public health clinics in Dhaka, Bangladesh. An urban clinic-based sample of 1309 currently married women of reproductive age presenting with abnormal vaginal discharge was recruited. Consenting women were interviewed and tested for Candida, bacterial vaginosis, Trichomonas vaginalis, Neisseria gonorrhoeae and Chlamydia tra-chomatis during a speculum examination. Approximately 53% (673/1309) of the participants had laboratory evi-dence of RTIs. The prevalence of Candida, bacterial vaginosis, T. vaginalis, N. gonorrhoeae and C. trachomatis were 32.4%, 22.4%, 3.1%, 2.1 %, 1.9% respectively. Age, education, living in a slum, working outside the home, polygamous marriage and suspecting infidelity were independently associated with vaginal and cervical infections. Candidiasis and bacterial vaginosis were the most common infections in this population. Paying attention to the socio-demographic and reproductive characteristics found to be associated with RTIs can assist clinicians in identi-fying women at risk of these infections. DOI: http://dx.doi.org/10.3329/seajph.v2i2.15958 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 67-72